Characteristics of private health insurance enrollees and the association between health coverage type and outpatient service utilization in Saudi Arabia: Insights from the National Saudi Family Health Survey - Khaled Shaeel Althabaiti; Monica Hunsberger; Jahangir Khan; Sayem Ahmed (PLoS ONE, 2026)
The Kingdom of Saudi Arabia (KSA) has a mixed health financing system consisting of governmental health coverage (GHC) and private health insurance (PHI). In 2016, KSA launched Vision 2030, which aims to reduce government spending and increase reliance on employer-sponsored PHI. This reform may affect the utilization of health services based on citizenship and the type of health coverage (PHI compared with GHC). The current study aimed to identify the characteristics of private health insurance enrollees and the association between different types of health coverage (GHC and PHI) and outpatient service utilization in the KSA. This study used data from the 2018 Saudi Family Health Survey (SFHS), which included 8,276 respondents aged 18 years and above and collected information on outpatient utilization during the previous 12 months. Statistical analyses were conducted using SPSS version 26. Bivariate analyses (chi-square and t-tests) were used to assess differences by nationality and coverage type. Binary logistic regression was used to examine the characteristics of PHI enrollment, and Poisson regression was used to evaluate the association between coverage type and outpatient utilization. This dataset provides a pre-reform baseline for assessing PHI enrollment and outpatient utilization prior to the implementation of the first phase of the reform in 2019. Most respondents were Saudi nationals (76.8%), and 54.9% were male. About 26.2% of respondents had PHI. Among non-Saudis, 72.8% were enrolled in PHI, compared with only 12.1% of Saudis. The logistic regression analysis revealed that having PHI was associated with factors such as a high monthly income, non-Saudi, male, being married, a high level of education, and a perception of good health. We found that having PHI was negatively associated with the utilization of outpatient services (coefficient −0.107; P < 0.001) compared with GHC. This finding may reflect barriers to access, a lower perceived need, or limitations in awareness of PHI benefits. In addition, this finding suggests that PHI may be associated with disparities in healthcare access, based on the observed lower utilization of outpatient services among its enrollees compared with those covered by GHC. Other factors associated with the utilization of outpatient services were being female, having a high monthly income, being never married, having chronic diseases, and the perception of poor health. The results of this study may inform future health reform efforts to enhance access to healthcare. These findings should be considered when planning the implementation and evaluation of the health system in KSA.